Modulation of sensitization processes in the management of pain and the importance of descending pathways: a role for tapentadol?. (3rd May 2020) - Caraci, Filippo; Coluzzi, Flaminia; Marinangeli, Franco; Mercadante, Sebastiano; Rinonapoli, Giuseppe; Romualdi, Patrizia; Nicora, Mariaflavia; Dickenson, Anthony H.
Abstract: Objective: This paper presents and discusses recent evidence on the pathophysiological mechanisms of pain. The role of tapentadol – an analgesic molecule characterized by an innovative mechanism of action (i.e. µ-opioid receptor [MOR] agonism and inhibition of noradrenaline [NA] reuptake [NRI]) – in the modulation of pain, and the most recent pharmacological evidence on this molecule (e.g. the µ-load concept) are also presented and commented upon. Methods: Narrative review. Results: Solid evidence has highlighted the importance of central sensitization in the transition from acute to chronic pain. In particular, the noradrenergic system holds a major role in limiting central sensitization and the progression to chronic pain. Therefore, pharmacological modulation of the noradrenergic system appears to be a well-grounded strategy for the control of chronic pain. Tapentadol is characterized by a to-date-unique mechanism of action since it acts both as a MOR agonist and as an inhibitor of NA reuptake. The synergistic interaction of these two mechanisms allows a strong analgesic effect by acting on both ascending and descending pathways. Of note, the reduced µ-load of tapentadol has two important consequences: first, it limits the risk of opioid-related adverse events, as well as the risk of dependence; second, the NA component becomes predominant at least in some types of pain with consequent specific clinical efficacy in the treatment of neuropathic and chronic pain. Conclusions: According to these characteristics, tapentadol appears suitable in the treatment of chronic pain conditions characterized by both a nociceptive and a neuropathic component, such as osteoarthritis or back pain.